Culture of fear and terrorism in Margaret Atwood’s MaddAddam trilogy - Milojevic, Natasa M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
Margaret Atwood’s Maddaddam trilogy depicts a civilization devastated by a lethal virus developed in a laboratory. The portrayal of isolated and marginalized individuals who perpetrate the construction of the virus, as well as the state of crisis and fear immanent to the apocalyptic narrative, lead to the analysis of the trilogy in reference to the social conditions following the 9/11 terrorist attacks. The New historical conception of literature as an equal participant of the process of circulation of the historical and cultural practices provides grounds for the interpretation of the novels within the field of a public imaginary which stems from the equalization of the terrorist threat with undefeatable contagious diseases. However, the trilogy’s cooperation with the system it attempts to uncover will hinder its subversive property and a critical distance. Despite its employment of parody in order to unveil the system, the trilogy (re)enforces the space where fear and apocalyptic thought dwell, therefore obstructing its separation and corroborating the culture of fear and terror it originated from.
Keywords: MaddAddam; culture of fear; terrorism; New Historicism; Margaret Atwood